Estudio del mecanismo de gelatinización del almidón nativo de banano exportable del Ecuador. - Martínez Mora, Omar (2015)
The Ecuador is among the leading producers and exporters of bananas countries worldwide. Figures from the production of this fruit in 2013 demonstrate the importance that represents this agricultural product for Ecuador. Banana exports constitute 32% of world trade in this fruit and 3, 84 % of total gross national product. From the above, the objective of this paper is study the mechanism of native starch gelatinization of exportable bananas Ecuador, temperature degree of gelatinization and pasting, considering the varieties: Cavendish, Filipino, Valery and Orito and its potential to be added in foods that claim desirable functional features such as thickeners, gelling agents and stabilizers. The methodology for finding these conditions were Scanning Electron Microscopy (SEM), the differential scanning calorimeter (DSC) and viscoamylographic (BRABENDER). According to the results, the native banana starch varieties studied can be incorporated into food processing demanding technological (thicke¬ners, gelling agents and stabilizers).